Necrotic central retinitis due to the lupus erythematosus - Orska, Małgorzata; Formińska-Kapuścik, Maria; Słoka, Adam; Kryśków-Bodzioch, Monika; Swadźba, Jakub (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
We present a case of a twenty six years old patient who had been treated for systemic lupus erythematosus (SLE) for five years. The patient developed a sudden significant disturbance of vision quality of both eyes. A lot of additional examinations were done and central necrotic retinitis was diagnosed. After treatment insignificant improvement of vision quality of both eyes was achieved.